Overview of clinical, molecular, and therapeutic features of Niemann–Pick disease (types A, B, and C): Focus on therapeutic approaches - Hosseini, Kamran; Fallahi, Jafar; Razban, Vahid; Sirat, Reyhaneh Zayyani; Varasteh, Mahnaz; Tarhriz, Vahideh (Cell biochemistry and function, 2024)
Niemann–Pick disease (NPD) is another type of metabolic disorder that is classified as lysosomal storage diseases (LSDs). The main cause of the disease is mutation in the SMPD1 (type A and B) or NPC1 or NPC2 (type C) genes, which lead to the accumulation of lipid substrates in the lysosomes of the liver, brain, spleen, lung, and bone marrow cells. This is followed by multiple cell damage, dysfunction of lysosomes, and finally dysfunction of body organs. So far, about 346, 575, and 30 mutations have been reported in SMPD1, NPC1, and NPC2 genes, respectively. Depending on the type of mutation and the clinical symptoms of the disease, the treatment will be different. The general aim of the current study is to review the clinical and molecular characteristics of patients with NPD and study various treatment methods for this disease with a focus on gene therapy approaches. Significance statement This work concerns an overview of Niemann–Pick disease (types A, B, and C) of clinical, molecular, and therapeutic features (focus on therapy approaches especially gene therapy).